Implementation of a CCSDS-based telemetry and telecommand system for LEO satellites - Lim, Soy Hiok. (2008)
Telemetry and telecommand operations are essential operations of the satellite as it allows the satellite in orbit to be properly monitored and controlled. A communication protocol is mandatory to conduct telemetry and telecommand operations. The CCSDS is an international organization that was set up in the mid 1980's to develop a set of communication protocol to handle space data. The CCSDS Packet Telemetry and packet Telecommand are amongst the recommendations made. Protocol architecture has been developed and issues like data error protection, frame structures are addressed.